Life Skills Education Implementation in Increasing the Autonomy of 21st-Century Santri at Pondok Pesantren Al-Machfudzoh, Jabon Sidoarjo - Firda Sari; Abd. Muhith; Erma Fatmawati (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
The 21st century known as the period of globalization has had so much influence on the life sector. The education sector is no exception; the period of globalization is marked by the mingling of western culture and the rapid development of technology and qualified expertise in various work and industry sectors. They are making it a new challenge for Islamic boarding schools or pondok pesantren that must maintain their existence in carrying out their duties and responsibilities as an institution that provides not only religious provisions but also skills and praxis for santri in facing the 21st century. This study uses a qualitative research approach with the type of case study. The implementation of life skills education in increasing emotional, behavior, and cognitive autonomy contained various pesantren activities such as development activities: al- banjari, computer mastery, scouts, English club, keputrian, karate, and PGPQ program. There are life skills educations in implementing self-development programs, namely personal and social skills, including general and specific ones.